Engineering tools for environmental risk management. 1, - Gruiz, Katalin; Meggyes, T.; Fenyvesi, Éva (CRC Press/Balkema, 2014)
This is the first volume of the five-volume book series "Engineering Tools for Environmental Risk Management", dealing with the following topics: types and management of environmental deterioration, particularly pollution; environmental toxicology as a versatile tool in monitoring and risk management; risk assessment of chemical substances and contaminated land; risk reduction measures, focusing on bio- and ecotechnologies; case studies demonstrating the interaction between regulation, management and engineering and the individual application of engineering tools.
Keywords: Ecosystem services.; Ecosystem services -- Social aspects.; Ecosystem services -- Government policy.; Pollutants.; Environmental risk assessment.; Environmental management.; Environmental engineering.; Environmental toxicology.; elektronické knihy; electronic books